Reatividade vascular no repouso e durante o exercício dinâmico máximo e seu impacto na perda de força muscular e na capacidade de exercício na insuficiência cardíaca com fração de ejeção reduzida - Arêas, Guilherme Peixoto Tinoco (Universidade Federal de São Carlos, 2019)
Chronic heart failure (CHF) entails helmark exercise intolerance and it is explained and it is explained by various systemic disfunctions. Recently studies have been shown that the flow-mediated dilation (FMD) of brachial artery has been used as non-invasive methods to assess the physical rehabilitation effects and such as the prognostic marker. Considering the necessity to identify studies to provide evidence about FMD technique and the effects on physical training on CHF patients, the first study had the aim of survey on the FMD technique, pathophysiological changes and the effect of rehabilitation on endothelial function (Study I). Among the studies, none addressed the acute impact of maximal dynamic exercise on vascular function in the CHF, especially in those with reduced cardiac contractility through reduced ejection fraction (HFrEF). The vascular dilatation capacity on the rest and after exercise could be explain the relationship between physical limitation and parameters from limited- symptons cardiopulmonary exercise test (CPX) (Study II). It was used 20 patients with HFrEF and 9 sex- and age–matched healthy controls. The volunteers perfumed endothelium function by FMD before and after CPX. The results showed that FMD on rest correlation with importants variables from CPX (V̇O2 peak, Circulatory power (CP), cardiac reserve and Chronotropic index). Furthermore, it was observed that only healthy subjects decreased FMD after exercise. Due to the intimate connection of the vascular system with skeletal musclecapacity to produce strength and endurance, the last two studies evaluated the relation of the muscular capacity with the capacity of exercise and its relation endothelial function (Studies III). It was recruited 23 CHF patients, being 12 mild dynapenic and 11 severe dynapenic. We observed that mild dynapenic patients have shown lower V̇O2 peak, higher V̇E/V̇CO2slope and CP, and worse V̇E/W rate. Moreover, the dynapenia gravity meant to more apperance of exercise ventilatory oscillation. Finally, the aim to investigate vascular dysfunction and their relationship with dynapenia gravity condition was realized in the last study (Study IV), which verify the maximum dynamic exercise impact on FMD. 22 patients participed in the study, being 11 patients separately to dynapenia group condition. Like the study II, ti was realized FMD before and after CPX. We observe at rest the same values of FMD in both groups. However, after exercise there was difference reponse between group, with deacrease values of FMD in mild dynapenic patients compared with no modifications in severe dynapenic group. These findings suggest that the ability to respond to exercise is impaired in those more severe patients. We conclude, therefore, that vascular function is important for understanding the evolution and severity of heart syndrome, as well as identifying the impairment in exercise capacity and muscle strength. Finally, we consider that the technique can be useful as evalutation of vascular reactivity on muscular disfunction, prognosis, as well as the possible effects of the physical rehabilitation of these patients.
Keywords: Insuficiência cardíaca; Função endotelial; Exercício; Treinamento físico; Músculo esquelético; CIENCIAS BIOLOGICAS::FISIOLOGIA